2023
DOI: 10.7554/elife.82978
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic profiling of the zebrafish inner ear reveals molecularly distinct hair cell and supporting cell subtypes

Abstract: A major cause of human deafness and vestibular dysfunction is permanent loss of the mechanosensory hair cells of the inner ear. In non-mammalian vertebrates such as zebrafish, regeneration of missing hair cells can occur throughout life. While a comparative approach has the potential to reveal the basis of such differential regenerative ability, the degree to which the inner ears of fish and mammals share common hair cells and supporting cell types remains unresolved. Here we perform single-cell RNA sequencing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 98 publications
(120 reference statements)
1
20
0
1
Order By: Relevance
“…For this purpose, precise analyses of the process for naturally occurring HC regeneration in the avian and fish auditory epithelia may be useful. Recent studies using single-cell RNA sequencing provide gene expression profiles of chick and zebrafish auditory epithelial cells in quiescent, degenerative, and regenerative status [ 90 , 92 , 93 , 94 , 95 , 96 , 97 ]. In contrast to mammalian cochleae, mammalian vestibular sensory organs retain the capacity for HC regeneration.…”
Section: Perspective For the Development Of Future Pharmacotherapy Fo...mentioning
confidence: 99%
“…For this purpose, precise analyses of the process for naturally occurring HC regeneration in the avian and fish auditory epithelia may be useful. Recent studies using single-cell RNA sequencing provide gene expression profiles of chick and zebrafish auditory epithelial cells in quiescent, degenerative, and regenerative status [ 90 , 92 , 93 , 94 , 95 , 96 , 97 ]. In contrast to mammalian cochleae, mammalian vestibular sensory organs retain the capacity for HC regeneration.…”
Section: Perspective For the Development Of Future Pharmacotherapy Fo...mentioning
confidence: 99%
“…Top, end organs in the horizontal plane; Bottom end organs in the saggital plane. Arrow heads indicate the general polarity of the hair cells in the epithelia, which change direction along the line of polarity reversal (LPR, dashed black line) in the otolith maculae ( Platt, 1993 ; Liu et al, 2022 ; Shi et al, 2023 ). There is no LPR in the cristae or macula neglecta.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish inner ear hair cells vary in their molecular signatures ( Barta et al, 2018 ; Hoffman et al, 2018 ; Shi et al, 2023 ). Using single-cell RNA sequencing, Shi et al, 2023 showed that hair cells from the inner ear have distinct genetic profiles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations